1978
DOI: 10.1007/bf02010764
|View full text |Cite
|
Sign up to set email alerts
|

A macromolecular inhibitor of in vitro calcification of tendon matrix

Abstract: Bovine and human tendon tissue do not induce calcification in vitro. However, extraction of those tissues with 3% Na2HPO4 converts them to calcifiable matrices. The supernatant fraction derived from the extraction contains a nondialyzable, perchloric acid soluble component that inhibits calcification of the extracted matrix. This inhibitory substance is characterized by a molecular weight in the range of 85,000-100,000. Exposure to pronase or hyaluronidase did not alter the inhibitory potency but did render th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…As Quittner and Wadkins pointed out (24), this change in the ligamentum flavum can be explained by the following two hypotheses: (a) phosphate specifically promotes dissociation from the tissue of substances that are calcification-inhibitory in situ, and (b) phosphate alone, or in combination with endogenous Ca2+, binds at appropriate sites of the matrix and thereby provides centers for nucleation and growth of calcium phosphate crystals. Although no evidence has been presented to indicate that the extract inhibits through the binding to the nucleation site of the matrix, the results of the present study suggest that the extract does have an inhibitory activity for matrix calcification in vitro.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As Quittner and Wadkins pointed out (24), this change in the ligamentum flavum can be explained by the following two hypotheses: (a) phosphate specifically promotes dissociation from the tissue of substances that are calcification-inhibitory in situ, and (b) phosphate alone, or in combination with endogenous Ca2+, binds at appropriate sites of the matrix and thereby provides centers for nucleation and growth of calcium phosphate crystals. Although no evidence has been presented to indicate that the extract inhibits through the binding to the nucleation site of the matrix, the results of the present study suggest that the extract does have an inhibitory activity for matrix calcification in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that the calcification inhibitor in bovine Achilles tendon has a peptidoglycan structure with a molecular weight of 85,000-100,000 (24). In the present study, although identification and measurement of the molecular weight was not possible because of the limited number of specimens, it was presumed to be greater than 8,000 from the exclusion limit of the cellulose dialysis tubing used, and the molecular weight of the protein obtained in the present method probably was smaller than that of protein extracted by use of protease inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interesting observation that normal tendon matrix does not mineralize in vitro [17] implies that changes in the structure or composition of tendon extracellular matrix are necessary for the development of hydroxyapatite deposits. Aging, diabetes, and injury likely alter tendon extracellular matrix so that calcification of matrix vesicles might occur.…”
mentioning
confidence: 98%